Building an enabling framework to promote community seed banks, harnessing four core elements: recognition, respect, support, and collaboration - Vernooy, Ronald; Subedi, Abishkar; Gupta, Arnab (2023)
Conclusion The number of community seed banks around the world is increasing, yet a substantive policy and legal void persists in many countries regarding their contribution to agricultural conservation and community development, and mechanisms to support, protect, and strengthen their function and activities. Recognizing the investment of time, effort, and resources that maintaining and sustaining a community seed bank requires, it follows that any established community seed bank would benefit from and indeed should not operate without a support strategy, including building from scratch and strengthening the necessary organizational and technical capacities needed to sustain its efficient functioning. Such a strategy could be designed and implemented at the policy, legal, and/or regulatory level. This brief offers key elements harnessing four dimensions of a collaborative strategy: recognition, respect, support, and collaboration.